Rapidly expanding venous intracerebral haemorrhage with spot sign. (23rd March 2018) - Funnell, Clark; Heran, Manraj K S; Teal, Philip; Field, Thalia
Abstract : A 79-year-old woman was brought to the hospital with an acute-onset left haemiparesis. On initial examination, she had a pure sensorimotor syndrome with left-sided weakness and sensory disturbance. Her mental status was normal. She had normal visual fields to confrontation and no neglect. Her initial CT and CT angiogram revealed cerebral venous thrombosis with associated haemorrhage. A 'spot sign' was visible on CT angiogram. Immediately following the CT scan, the patient had a rapidly progressive decline in level of consciousness, requiring endotracheal intubation. A follow-up CT scan 70 min later showed the haemorrhage had expanded dramatically, with mass effect, midline shift and herniation. After a discussion with the family, the patient was extubated and died the following day. This is the first case of a cerebral venous thrombosis with associated spot sign-positive haemorrhage and published clinical details that the authors are aware of.